Mitigating the Effects of Adverse Childhood Experiences: How Restorative Practices in Schools Support Positive Childhood Experiences and Protective Factors. Issue 3 (3rd July 2021) - Breedlove, Meghan; Choi, Jihyeon; Zyromski, Brett
ABSTRACT: Many students in the United States suffer from mental health issues resulting from Adverse Childhood Experiences (ACEs). Often, students exhibit negative behavior as a result of these issues and many schools continue to implement punitive approaches to discipline, such as suspensions or expulsions, which serve to further isolate and disconnect students from school. Positive Childhood Experiences (PCEs) and Protective Factors (PFs) can mitigate the negative effects of ACEs. In this paper, we suggest that restorative practices (RPs) in schools may be an integral component in promoting PCEs and PFs for all students. Documented outcomes of restorative experiences in schools are aligned with PCEs and PFs at the individual, interpersonal, and school-wide level. Considerations of RP implementation and implications for training teachers and mental health professionals conclude the manuscript.